Concise synthesis of phenanthrene derivatives via intermolecular TDDA reaction induced by tetrayne cyclization. (8th June 2022) - Liu, Baohua; Cao, Xiujun; Yan, Jingjing; Hu, Qiong; Hu, Yimin
Graphical abstract: A convenient and meaningful method for constructing multifunctionalized phenanthrene and naphthalene derivatives through the reaction of tetraynes with substituted phenylacetylenes by controlling reactant substituent electronic effect was reported. The reaction system has good chemoselectivity and provided a new way to generate phenanthrene and naphthalene compounds from simple and available materials under relatively mild conditions. The possible mechanism for two reaction model was proposed. Further exploit application of those compounds in materials and biologic activity is ongoing in our laboratory. Abstract: The facile construction of phenanthrene derivatives through the intermoletetradehydro-Diels-Alder (TDDA) reaction of benzyne in situ generated by the hexadehydro-Diels–Alder (HDDA) reaction with various substituted phenylacetylene was described. The naphthalene derivatives were obtained unexpectedly in another reaction modle when expanding substrate scope. The reaction profiles has good chemoselectivity and provided a new way for the synthesis of highly functionalized phenanthrene and naphthalene derivatives from simple materials under relatively mild conditions.